2019
DOI: 10.1186/s12888-018-1990-6
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a case definition for depression in administrative data against primary chart data as a reference standard

Abstract: BackgroundBecause the collection of mental health information through interviews is expensive and time consuming, interest in using population-based administrative health data to conduct research on depression has increased. However, there is concern that misclassification of disease diagnosis in the underlying data might bias the results. Our objective was to determine the validity of International Classification of Disease (ICD)-9 and ICD-10 administrative health data case definitions for depression using re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(80 citation statements)
references
References 22 publications
1
73
0
Order By: Relevance
“…Previous validation studies have shown that two or more claims for a medical condition tend to improve accurate identification of that medical condition . However, accurately identifying medical conditions depends on the number of years for the study period and the medical condition examined . A single claim‐based definition for identifying a pediatric‐onset disability and osteoporosis performs better compared with other medical conditions, with positive predictive values of approximately 80% and up to 92%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous validation studies have shown that two or more claims for a medical condition tend to improve accurate identification of that medical condition . However, accurately identifying medical conditions depends on the number of years for the study period and the medical condition examined . A single claim‐based definition for identifying a pediatric‐onset disability and osteoporosis performs better compared with other medical conditions, with positive predictive values of approximately 80% and up to 92%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…(25,44) However, accurately identifying medical conditions depends on the number of years for the study period (26) and the medical condition examined. (25,26,45) A single claim-based definition for identifying a pediatric-onset disability and osteoporosis performs better compared with other medical conditions, with positive predictive values of approximately 80% (25) and up to 92%, (26) respectively. Third, we did not account for potential confounding factors, such as ethnicity, geographic region, or other socioeconomic status variables (eg, education level).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research on data quality demonstrates that there are potential biases and other issues that need to be accounted for [19][20][21][22][23], and EHR data is no exception. Thus, a researcher must consider the following factors when attempting to design a study using EHR: Documentation in EHRs should be thorough and complete, as missing or incorrect information at this stage impacts the quality of downstream data.…”
Section: Understanding the Relationship Between Front End And Back Enmentioning
confidence: 99%
“…Our SMR estimates may be sensitive to outcome misclassification because of errors in coding claims and varying coding practices across participating hospitals. For example, a prior study [27] reported that administrative claims data have 61% sensitivity and 94% specificity for classifying depression when electronic health records are the reference standard. If outcome misclassification is precisely nondifferential (i.e.…”
Section: Discussionmentioning
confidence: 99%